1979
DOI: 10.1507/endocrj1954.26.337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral administration of positively charged insulin liposomes on alloxan diabetic rats: Preliminary study.

Abstract: Insulin encapsulated in liposomes of various lipid compositions were prepared. The amount of insulin trapped in these liposomes increased in the order, negatively charged liposomes less than neutral liposomes less than positively charged liposomes. In positively charged liposomes, the amount of insulin trapped increased with increase in the amount of amphiphile stearylamine. Under the conditions tested, the highest insulin content (about 50%) was obtained with liposomes composed of phosphatidyl choline/cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…smaller than 300 nm passed through Peyer's patches and entered the systemic circulation [Jani et al, 1990]. Hashimoto and Kawada reported that use of cationic liposomes improved the intestinal absorption of insulin [Hashimoto and Kawada, 1979]. Similarly, the findings of the present study also verified that not only the particle size but also the electrical charge of the inner liposomes in DL affects intestinal absorption.…”
Section: Effects Of the Electrical Charge Of Liposomes On Thesupporting
confidence: 83%
“…smaller than 300 nm passed through Peyer's patches and entered the systemic circulation [Jani et al, 1990]. Hashimoto and Kawada reported that use of cationic liposomes improved the intestinal absorption of insulin [Hashimoto and Kawada, 1979]. Similarly, the findings of the present study also verified that not only the particle size but also the electrical charge of the inner liposomes in DL affects intestinal absorption.…”
Section: Effects Of the Electrical Charge Of Liposomes On Thesupporting
confidence: 83%
“…Regarding liposome size, Aramaki et al reported that multilamellar liposomes (MLV) larger than 374 nm in size were taken up through rat Peyer's patches after oral administration using isolated tissues. 28 The MLV liposomes have been used in many cases for oral administration, [11][12][13][14][15] while REV liposomes have not.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] The use of liposomes as carriers of cytokines, 16 interleukin-2, 17 interleukin-7, 18 and interferon 19 has been reported, but that of Epo has not been studied in the past.…”
mentioning
confidence: 99%
“…The infusion systems for insulin have also been developed (2 These include the finding of new insulin derivatives (4-61, a suitable dosage form (7,8) and a proper drug carrier which 1s stable in the gastrointestinal fluids such as the entrapment of the hormone in liposomes (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Insulin together with soybean trypsin inhibitor has been directly injected to rat ileum resulting in a significant drop in blood glucose (7).…”
Section: Introductionmentioning
confidence: 99%
“…Varying of these physical properties can also affect the location and the rate of metabolism of the liposomes as well a s the drugs being entrapped. Recently, an extensive investigation on t h e use of liposomes as carriers for the introduction of insulin via the oral route has been focussed (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%